Islam and politics in Malaysia since 1957: fluctuation between moderation and radicalisation of the state, society and religion - Akhmetova, Elmira (University of Management and Technology, Lahore, Pakistan, 2019)
This paper discusses the relationship in post-independence Malaysia between the state, civil society and the country’s dominant religion, that is, Islam. When Malaya obtained independence from the British in 1957, many expected that Islam would lead to social and economic decline. The constitution states that Islam is the state religion, although it also states that religious freedom for non-Muslims is assured without discrimination. Since then, religious affairs have remained a state responsibility and Malaysia has been hailed for decades as an oasis of moderate Islam. However, during the last few years religiously motivated hatred has become prevalent and popular in Malaysia for many reasons. This paper underlines the factors that have led to the growth of hate and the decline of the moderate Islam previously found in Malaysia. It proposes that the radicalisation of Malaysian Muslims should be evaluated within the framework of current geopolitics and the impact on the well-being of the Muslim world, rather than localising it into regional and national faults. The paper argues that Islam in Malaysia is an instrument that shapes the political behaviour of the public and the ruling elite. Lastly, the paper proposes that effective governance and ensuring that citizens’ rights are respected are some of the most effective ways of eliminating extremism and preventing radicalisation